Vasculitic Neuropathy: A Retrospective Analysis of Nerve Biopsies and Clinical Features from a Single Tertiary Care Center - Hui, Monalisa (Ann Indian Acad Neurol, 2019)
OBJECTIVE: Vasculitic neuropathy can be either restricted to the peripheral nerves or associated with systemic involvement of other organs. The objective of this study was to analyze the nerve biopsies reported as “vasculitic neuropathy” with clinical features. MATERIALS AND METHODS: All cases diagnosed with vasculitic neuropathy were retrospectively analyzed and categorized as systemic vasculitis and nonsystemic vasculitic neuropathy based on the clinical features. The histological features were further evaluated and classified according to the Peripheral Nerve Society Guidelines. RESULTS: Of the 126 cases, there were 65 nonsystemic vasculitis, 45 secondary systemic vasculitis, and 16 primary systemic vasculitis. Definite vasculitis was more common in the systemic vasculitis group. The epineurial vessels were predominantly involved with chronic axonal changes. CONCLUSION: The sensitivity of definite vasculitis on nerve biopsy was 54.76%. The sensitivity increases when the diagnostic criteria of definite and probable vasculitis were applied taking into account perivascular inflammation accompanied by vascular changes and axonopathy.